Spectrum sensing based on deep learning with fading channels - Xu, Aofan (Nanyang Technological University, 2024)
With the development of fifth generation (5G) and sixth generation (6G), more devices will be accessed in the channel, spectrum resources will be continuously occupied, and there is currently almost no unallocated spectrum. However, spectrum is a limited resource, and due to technical limitations, it is difficult to expand spectrum, leading to the current spectrum shortage. Nevertheless, the utilization rate of existing spectrum is not high and there are often gaps in the spectrum.